PENGARUH MEDIA GAMBAR SERI TERHADAP KEMAMPUAN MEMBACA PERMULAAN DI KELAS II SANGGAR BELAJAR KAMPUNG BHARU MALAYSIA - Tri Mutiara Atmaja; Mandra Saragih (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study examines the effect of picture series media on the beginning reading ability of second grade students at Sanggar Belajar Kampung Bharu Malaysia. Using an experimental research design with a quantitative approach, this study involved 15 second grade students as both the population and the sample. Data collection techniques included observation sheets and tests to measure students' beginning reading ability. This study used a non-equivalent group design to investigate differences in results before and after treatment. The findings of the study showed a significant difference between the pretest (mean value: 64.06) and posttest (mean value: 82.13), showing an increase of 18.07 points after the application of picture series media. The paired t-test analysis showed a significance value of 0.000 (p <0.05), confirming that picture series media had a significant effect on beginning reading ability. Before treatment, only 3 students achieved scores above the minimum completion criteria (KKM> 70), while after treatment, 14 students scored above the KKM limit. This study proves that picture series media effectively improves students' early reading skills by providing visual representations that increase motivation, stimulate imagination, and help students connect letters with meaningful concepts. This study provides valuable insights for elementary school teachers in choosing the right media to improve early reading instruction